TRANSFORMASI KEMITRAAN BISNIS: INOVASI PLATFORM INFLUENCER MARKETING CERDAS UNTUK MENDUKUNG KOLABORASI EFEKTIF ANTARA UMKM DAN INFLUENCER - Syifa Alina Amri; M. Rizaldi; Putu Pradnya Shita Ambhika; R. Aditya Rayhan Zanesty; Nabila Nanda Dwi Cahya; Mahendrawathi ER (Komunitas Menulis dan Meneliti (Kolibi), 2023)
MSME have always had to spend large amounts of time, effort, and thought to conduct the influencer marketing process which do not always produce clear outcomes. Meanwhile, influencer marketing has a large potential to drive business success as 92% of people trust product reccomendations which are common in influencer marketing (Talaverna, M. 2015). The development of Digiflux, an Artificial Intelligence (AI) based influencer marketing platform, is the purpose of assisting MSMEs in finding suitable influencers for their business. Digiflux offers three main values; effectivity of finding suitable influencers, time efficiency, and the impact towards successful product promotion. The AI technology being developed can fulfill the needs of MSMEs in influencer matching, fraudulent followers detection, and sentiment analysis in one integrated platform. The method of development used a qualitative research through survey for 73 MSMEs and interview to. 17 MSMEs. Afterwards, the results obtained are used to develop the business and platform. The early iteration stage of the business process is done in order to produce a dataset for development of the machine learning model that will be implemented on Digiflux’s AI technology. With the use of AI, Digiflux gains a strong competitive advantage in the market such that a sustainable business can be formed. The use of Digiflux’s services has helped improve the business performance of MSMEs including rise of brand awareness rate up to 420% as shown by the increase of social media followers. The realization of Digiflux is hoped to bring a drastic improvement for MSMEs in Indonesia.